Hemorrhoid management in women: the role of tribenoside + lidocaine - Jan Kestřánek (BioExcel Publishing Ltd, 2019)
Hemorrhoids are commonly reported in women. However, despite the high prevalence of hemorrhoids in women and the major impact of this condition on quality of life, specific evidence and recommendations on the treatment of hemorrhoids in women are scant. This paper reviews various options in current therapy for hemorrhoids in women-namely, medical intervention (topical and systemic drug therapy)-and discusses the available clinical evidence for an appropriate use of over-the-counter topical formulations for the symptomatic treatment of hemorrhoids. Its focus is on a medical preparation containing tribenoside + lidocaine, available as a rectal cream (tribenoside 5%/lidocaine 2%) and a suppository (tribenoside 400 mg/lidocaine 40 mg) and marketed under the brand Procto-Glyvenol® (Recordati, SpA, Italy). Given its rapid comprehensive efficacy on all the different symptoms of hemorrhoids, the tribenoside + lidocaine combination can find a place in the treatment of this hemorrhoidal disease. Importantly, its efficacy and tolerability have been formally evaluated in several well-conducted studies, some of which were specifically conducted in women. In particular, tribenoside + lidocaine can be safely administered in postpartum women and in pregnant women after the first trimester of pregnancy. In pregnant women, the tribenoside/lidocaine combination significantly improved both subjective and objective symptoms of hemorrhoids. Fast onset of symptom relief was reported from 10 minutes after administration, lasting up to 10-12 hours. On these bases, tribenoside + lidocaine can represent a fast, effective, and safe option to treat hemorrhoids when conservative therapy is indicated, and it deserves consideration as a first-line treatment of this disease in clinical practice.